Interest Groups and Health Care Reform Across the United States - Virginia Gray, David Lowery (Georgetown University Press, 2013)
This book is about the politics of interest representation. It is also about health care policy and politics in the American states. But it is first and foremost a book about interest representation. Simply put, there is a deep and profound debate among both academics and citizens about the role interest organizations play in the public policy process (Lowery and Gray 2004b). On the one hand, the press routinely recycles stories of undue influence of narrow, selfish special interest groups, highlighting their privileged position in American politics. In academic discussions, this view is sometimes labeled the transactions perspective because it suggests that much of politics is about the purchasing of public policy. These special interests glide through the supermarket of the public policy process, placing their preferred policies in a market basket, and then proceed to the checkout counter to pay in the currency of campaign contributions, promised employment for politicians in postelectoral careers, or simply favors among overly convivial good old boys (Schattschneider 1960). From this perspective, organized interests pose a direct and material threat to democratic government.